Ten tips for publishing a scientific article - Braslavsky, Ana; Hernández, Rolando J.; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2026)
Publishing a scientific article is essential for sharing knowledge, advancing academic careers, and fostering professional growth. This article presents ten practical recommendations to support successful scientific publishing. It emphasizes the importance of planning the manuscript early, clearly defining objectives and target audiences, and preselecting suitable journals. Choosing the right journal—considering its scope, requirements, indexing, and impact factor—is critical. The article also highlights the need to follow author guidelines, structure the manuscript appropriately, uphold scientific integrity, and present findings clearly. Finally, it encourages authors to be patient with editorial timelines, appreciate reviewer feedback, and seek support from colleagues. These strategies aim to increase the chances of publication and support a strong academic trajectory.
Keywords: Medical Writing; Peer Review; Research; Manuscripts as Topic; Publications; Article